1996
DOI: 10.1192/bjp.168.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Drug Induced Psychosis

Abstract: ROBPOOLEand CLAREBRABBINS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 27 publications
3
32
0
3
Order By: Relevance
“…5 Our interpretation of our findings, together with similar studies, would tend to support these assertions. It was also predicted that, despite these problems, the diagnosis was likely to continue to be used.…”
Section: Limitationssupporting
confidence: 68%
See 1 more Smart Citation
“…5 Our interpretation of our findings, together with similar studies, would tend to support these assertions. It was also predicted that, despite these problems, the diagnosis was likely to continue to be used.…”
Section: Limitationssupporting
confidence: 68%
“…[1][2][3] This has revived interest in the nature of the conditions that attract the clinical diagnosis of druginduced psychosis. 4 The concept of drug-induced psychosis has been criticised 5 and it remains unclear whether the diagnosis reflects a valid diagnostic category or whether it is based on arbitrary assumptions regarding the causation of symptoms. A systematic review concluded that the inference of causation is not secure and that the condition Aims and method To assess the stability of the diagnosis of first-episode druginduced psychosis over a follow-up period of at least 2 years.…”
mentioning
confidence: 99%
“…However, the scientific debate about amphetamine-induced psychosis is ongoing, and it remains unclear whether the use of amphetamine-like substances can actually cause a psychotic disorder in an otherwise healthy individual, or whether it triggers the onset of schizophrenia in an individual with high vulnerability to the disease (Phillips & Johnson, 2001;Poole & Brabbins, 1996). Increased drug use among psychotic patients may also result from their attempt to counteract nonspecific physical symptoms or side effects of neuroleptics (Mueser, Drake & Wallach, 1998).…”
Section: Khat and Psychosis: Theoretical Backgroundmentioning
confidence: 99%
“…However, some commonly reported views did not appear to be based on scientific knowledge: for example, most felt that 'drug-induced psychosis' was a valid diagnosis despite a lack of empirical evidence to support the utility of this construct. 8 It is also worth noting that the prognostic factors given most weight by participants were those related to service user's behaviour ('substance misuse' and 'concordance'). However, remarkably few inter-group differences in the views relating to firstepisode psychosis between adult and child psychiatrists were elicited, despite working in markedly different subspecialties.…”
Section: Discussionmentioning
confidence: 99%